LEGAL PROTECTION BY HOSPITALS AGAINST VIOLENCE EXPERIENCED BY DOCTORS - Sulyaprilawati Battri Siahaan; Henry Aspan; Marice Simarmata (RADJA PUBLIKA, 2025)
This normative legal study aims to examine legal protection for doctors who are victims of violence in hospitals in Indonesia. Using a normative legal approach based on an analysis of legislation, legal doctrine, and academic literature, this study identifies a discrepancy between the normative legal protection provisions and their implementation in hospital institutional practice. The research findings indicate that acts of violence against doctors, whether verbal, psychological, or physical, are structural problems and correlate with the suboptimal legal protection system at the hospital level. Although Law Number 17 of 2023 concerning Health explicitly recognizes doctors' right to legal protection in carrying out their profession, in practice, hospitals still tend to limit this protection to administrative aspects and have not yet established a comprehensive legal protection mechanism. Effective legal protection has been shown to contribute directly to increasing doctors' sense of security, maintaining professional independence, and improving the quality of health services. Thus, strengthening institutional legal protection for doctors is a fundamental prerequisite for the realization of safe, quality, and equitable health services.